Pembuatan Peta Administrasi Desa Tabing Berbasis Sistem Informasi Geografis (SIG) sebagai Upaya Mendukung Tertib Administrasi dan Perencanaan Pembangunan Desa - Adeswastoto, Hanantatur; Desrimon, Arfi; Islah, Muhammad; Alisa Putra, Agus; Alenya, Nia (Journal of Social and Community Service, 2026)
Tabing Village, Koto Kampar Hulu Subdistrict, Kampar Regency, Riau Province did not yet have an official and informative administrative map, even though such a map is essential for orderly administration and village development planning. This community service activity aimed to produce an administrative map of Tabing Village based on Geographic Information System (GIS) as a contribution from an academic team of the Civil Engineering Study Program to the village government. The method used was cartographic digitization based on secondary data, namely the 2023 Indonesian Base Map (RBI), 2022 BING Imagery, and 2025 Planetscope Imagery, using the Universal Transverse Mercator (UTM) Zone 47N projection and the WGS 1984 datum. The output was an administrative map at a scale of 1:35,000 depicting administrative boundaries, road networks, rivers, settlement distribution, and public facilities. The map was handed over as a reference document for the Tabing Village government and is expected to support orderly territorial administration and more directed village development planning.